The variability leave signs generative sprout of the plowed clover Trifolium arvense L. in the conditions of Dagestan - M. Z. Gamzatova; A. D. Habibov (Юг России: экология, развитие, 2015)
The variability leave signs generative sprout of the plowed clover Trifolium arvense L. is studied on high-altitude factor during three years, which collections were conducted from the two extreme heights (100 and 2100 m.) in the conditions of Dagestan. The role of the every year’s conditions of the regrowing place and the high-altitude factor in the variability of the statistic signs is marked. The essential correlative relationships of the high-altitude gradient with the registered signs are revealed. The significances of the strength of the influence and the coefficient of the determination on both factor (the years of the collection of the material and the height above the sea level) and also their interaction.